Development of automatic control oil palm cutter - Abdul Rahim, Rahimi; Wan Ismail, Wan Ishak (Universiti Putra Malaysia, 1999)
An automatic cutter for harvesting Fresh Fruit Bunches (FFB) use in the oil palm plantation was design and fabricated at Faculty of Engineering, UPM. This cutter was suitable for short oil palm trees of between 4 to 5 years old. The cutter was design to be portable easily attached to a tractor by three-point link attachment. This cutter consisted of sharp bar to hold the oil palm FFB and cutting tool to cut the FFB. Two methods of cutting and harvesting the FFB were tested. The first concept is by cutting the FFB's stem and at the same time turning the FFB more than 3600. The other method of harvesting is only by cutting the FFB‟s stem. Hydraulic system was used as a power source to actuate the cutter. In order to automate the cutter, Programmable Logic Control (PLC) and limit switches were used. This cutter also can be an end-effector for the agricultural robot use in the oil palm plantation.